The Contemporary Interpretations of the Second of Aquinas's Five Ways - Haji Salleh, Kamarudin (Jurnal Usuluddin, 1998)
This short article aims at delineating the contemporary interpretations of the second Aquinas's five ways. There are two tendencies among the twenties-century philosophers in approaching the issue. The philosophers like Kenny and Flew seem criticize and reject the second way argument to proof the existence of God. On the other hand, Velecky, Copleston and Craig claim that earlier is mis-under stood and take the proof out of their context in Aquinas's thought.